Innovation of glow-in-the-dark roadside lines in rural area / Muhammad Amirul Syazwan Muda and Muhammad Naim Mahyuddin - Muda, Muhammad Amirul Syazwan; Mahyuddin, Muhammad Naim (2023)
Road safety in rural areas is a pressing concern due to high rates of motor vehicle mortality, increased fatality risk with limited access to hospitals, and high severity of injuries. Additionally, accidents caused by poorly lit roads, making its users to have limited visibility, will increase the challenges for emergency vehicles on narrow roads, and inadequate street lighting will further exacerbate the issue. To overcome the road safety issues in rural areas, it requires improving the existing road infrastructure, implementing sustainable road lighting solutions, enhancing electricity accessibility, and promoting road safety education and enforcement. Therefore, this research is aimed to develop glow-in-the-dark roadside lines in rural areas to reduce the number of road accidents. To achieve the aim, four objectives have been established which are to develop innovative design ideas for glow-in-the-dark roadside lines in rural areas, assemble a mock-up model based on the improved designs, assess its performance, and demonstrate entrepreneurial skills in proposing a marketable solution.